Effect of Foliar Fertilization with a Mixture of Microelements and Yeast Extract on some Qualitative, Productive Properties of Grapevine (C.V. Al-Helwani) (Journal of Hama University, 2022)
The study was conducted during the 2021 season in a private orchard in Deir Hafer, east Aleppo, the research aims to study the effect of foliar fertilization with a some microelements (Fe-B-Mo-Cu-Mn-Zn) concentrated (0.5-1-1.5 grŁ) and dry yeast extract concentrated (10-15-20 grŁ) during different growth stages in the productivity of the grapevine (C.V.Al-Helwani) and the quality of the fruits .The results showed the superiority of the dry yeast extract at a concentration of (20 grŁ) and the mixture of microelements at a concentration of (1.5 gŁ) significant differences in terms of the average diameter of the fruit, the percentage of soluble solids and the flavor factor, which were, respectively, (2.7cm-14.9%-69.6) and (2.65cm-15.0%-67.7) in order compared to the control (2.17cm-12.2%-46.7).Also, the yeast treatment at a concentration of (20 grŁ) was superior to all treatments in terms of the weight and size of the fruit clusters and the production quantity, respectively (1.34kg-1191.7cm3-74.2kg) straight compared to the control (0.5kg-259.8cm3-25.9kg), Whereas, the yeast treatment was also superior to the concentration (20 gr/l) on the rest of the treatments in terms of reducing sugars and pH of fruit juice (14.6%-5.0) compared to the control (12.2%-3.9), while the total acidity (T.A) decreased when sparing with yeast at a concentration of (20 grŁ) reaching (0.21%) compared to the control (0.26%).
Keywords: Foliar Fertilization, Dry Yeast, Stomach element combination, Productive, Fruit quantity, Helwani grapes